Prevalence of Implants in Jeddah City and socio demographic factors associated with it. - Abdullah Rabee Alghtany; Moayad Ahmed Bedaiwi; Muath Muhammad Benten; Amjad Khaled Alkhanbashi; Lujain Jabber Alkhattabi (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2019)
Introduction: In the past two decades, dental implants have become a widely accepted and implemented therapeutical method to replace missing teeth and support fixed and partially removable prostheses. High long-term survival rates have been reported both for systemically healthy (cumulative survival rates of 83.8% after 25 years, 96.1% after 10 Methods: This retrospective study was conducted in the Dental college of Jeddah. In this study, all the dental implants which were placed during June 2017–April 2018 the patients having dental problem included in this study. Results: 34% of the dental patients undergoing the Implant Process, males are dominating Conclusion: These findings provide valuable information for workforce development and for the implant industry to allocate resources for the anticipated future demand among patients eligible for implant treatment yet not receiving it.